Detectability of BI-RADS category 3 or higher breast lesions and reading time on mammography: comparison between 5-MP and 8-MP LCD monitors. - Yabuuchi, Hidetake; Kawanami, Satoshi; Kamitani, Takeshi; Matsumura, Tomomi; Yamasaki, Yuzo; Morishita, Junji; Honda, Hiroshi (Acta Radiologica, 2017)
Background Five-megapixel (MP) displays are recommended as soft copy devices for digital mammogram. An 8-MP liquid crystal display (LCD) (two 4-MP displays within one display) might offer the advantage of being able to view biplane mammography more easily than the dual planes of 5-MP LCDs. Purpose To compare detectability of Breast Imaging Reporting and Data System (BI-RADS) category 3 or higher lesions and reading time on mammography between 5- MP and 8-MP LCDs. Material and Methods The mammograms of 240 breasts of 120 patients including 60 breasts with BI-RADS category 3 or higher lesions and 180 breasts with normal or category 2 lesions were enrolled. All bilateral mammograms were displayed on bifacial 5-MP LCDs or an 8-MP LCD (two 4-MP displays within one display). Six radiologists assessed 240 breasts on each display. The observations were analyzed using receiver operating characteristic (ROC) analysis. A jack-knife method was used for statistical analysis. We employed a paired t-test to determine whether any significant differences existed in the reading time between two different displays. A P value < 0.05 was considered significant. Results The mean areas under the ROC curve obtained using 5-MP and 8-MP LCDs were 0.925 and 0.915, respectively, and there was no significant difference ( P = 0.46). There was also no significant difference in the reading time between two types of displays (57.8 min. vs. 51.5 min, P = 0.39). Conclusion The detectability of BI-RADS category 3 or higher lesions and reading time using an 8-MP LCD were comparable to those using a 5-MP LCD.